BUILDING EARLY CHILDHOOD LEARNER’S VOCABULARY BY USING BBC LEARNING ENGLISH VIDEO - Mia Febriana (Universitas Negeri Padang, 2017)
Vocabulary is important aspects in language learning that learners must achieve in order for them to be able to communicate in English. BBC Learning English video is one of the alternative tools that can be used by early childhood learner to build their vocabulary. This research aimed to draw the use of BBC Learning English video for building early childhood learner’s vocabulary. The study employed qualitative research design. The method of this study was case study. The subject of this study was a three-year-old child. The collection of the data was through observation. The researcher asked the child to watch BBC Learning English video and guided the child to memorize the vocabulary on it by repeating the vocabulary. The data revealed that BBC Learning video gave positive impact on building early childhood learner’s vocabulary. By using BBC Learning English video, a three-year-old child could build his English vocabulary. Moreover, the video also helped the child to pronounce new vocabulary. The implication of this research was early childhood learner is able to produce new English vocabulary.